Stimulation of hair growth using conditioned media derived from dental pulp stem cells expanded in serum free media / Tarini Nawamalie Abeysinghe Gunawardena - Tarini Nawamalie, Abeysinghe Gunawardena (2017)
Introduction: Alopecia is a clinical condition caused by the hair loss and may result in baldness. The current treatment methods for this condition involve the use of drugs or natural substances. However, hair loss may be accelerated upon the discontinuation of medication. Alternatively, alopecia surgery could also be carried out though it has its limitations in the number of surgeries and the number of hair strands transplanted. Stem cell therapy, a recently emerged approach for alopecia treatment involves tedious procedures, complicated safety and quality management, low survival rate of transplanted cells and potential adverse immunological responses for the recipients. As an alternative, use of paracrine factors secreted by the stem cells showed promise in therapeutic applications. Paracrine factors involved in regulation of hair growth have been observed to be secreted by stem cells, in the culture media, termed as conditioned media (CM). Objectives: In this study we first verified the mesenchymal stem cell (MSC) like properties of human exfoliated or extracted deciduous dental pulp (SHED) and hair follicle stem cells (HFSCs) cultured in different concentrations of serum supplemented in DMEM-KO and in chemically defined media namely, STK2 (TwoCELLs, Japan). Secondly, hair growth regulatory paracrine factor profiles of CM prepared through culture of SHED and HFSCs in the respective media were ascertained. Lastly, the potential of SHED- and HFSC-CM to stimulate hair growth under in vitro and in vivo conditions were evaluated. Methods: SHED (n=3) and HFSCs (n=3) were cultured in, STK2 and other media combinations; DMEM-KO+10% FBS, DMEM-KO+10% FBS+bFGF, STK2+2% FBS and profiled for the presence of positive hair regulatory factors namely SDF-1, VEGF, HGF, PDGF-B and negative hair regulatory factors namely TGF-β, bFGF, TNF-, IL-1 and BDNF. The potential of the prepared CM to stimulate hair growth was evaluated based on the paracrine profile and the observed in vitro hair growth dynamics. The administration of the CM media via subcutaneous injection to telogen-staged synchronized 7-week old C3H/HeN female mice was carried out to further study the potential of the CM to stimulate hair growth in vivo. Results: SHED and HFSCs maintained their MSC characteristics in all media combinations. Cells cultured in STK2 based media showed better population doubling time, higher viability and better maintenance of MSC characteristics in comparison to cells cultured in DMEM-KO based media. SHED and HFSCs showed higher growth kinetics at passages 3 and 4. Cells cultured in DMEM-KO based media showed a higher expression of positive hair regulatory factors; SDF-1, VEGF, HGF, PDGF-B than cells cultured in STK2 based media. However, the difference was not statistically significant. Moreover, STK2 based CM contained only two negative hair regulatory factors, TNF-, IL-1 while DMEM-KO based CM media contained all negative hair regulatory factors that were tested. The in vitro studies confirmed that treatment with CM of passage 3 cells prepared in STK2 based media resulted in a significantly higher number of anagen-staged hair follicles (p< 0.05) and a significantly lower number of telogen-staged hair follicles (p< 0.05). Administration of SHED-CM prepared in STK2 to C3H/HeN mice resulted in a significantly faster stimulation of hair growth in comparison to the HFSC-CM prepared in STK2 (p< 0.05). Conclusions: Within the limitations of the study, STK2 is a better media for the expansion of both SHED and HFSCs and the maintenance of stem cell characteristics in comparison to DMEM-KO based media. SHED-CM prepared using STK2, significantly enhanced the stimulation of hair growth compared to HFSC-CM.